OPTIMASI BLOG DENGAN META TAG UNTUK SEO DAN MONITORINGNYA - Valian Yoga Pudya Ardhana; Ahmad Wilda Yulianto (Universitas Bumigora, 2015)
Blog as one of the media applicationson the Internethas been used all aroundIndonesia. The user wasnot limited by age,ranging from children to the elderly. A lot of people notrealize that blogs can beoptimizedso thatthe bloggettingtoppositionsin search engines. Metatagwasone ofoptimization techniquesinSearch Engine Optimization (SEO). The main target washow to increaseblogtraffc requests. Afteroptimization, the next stepwasmonitoring, whichaims to determinethe extent to whichthe success ofoptimizationhas been done onSEO.The resultwas ablog sitegettingtoppositionsinthe search enginesandthe monitoring process resultsindicatethat thetitleand content was veryappropriatethat was 100%, description and contentwere alsoappropriatethat was 91%.